Randomized Trial of an Improved Drainage Strategy Versus Routine Chest Tube After Lung Wedge Resection - Zhang, Jia-Tao; Dong, Song; Chu, Xiang-Peng; Lin, Shao-Min; Yu, Run-Ying; Jiang, Ben-Yuan; Liao, Ri-Qiang; Nie, Qiang; Yan, Hong-Hong; Yang, Xue-Ning; Wu, Yi-Long; Zhong, Wen-Zhao (The Annals of thoracic surgery, 2020)
Patients undergoing thoracic lung wedge resection could benefit from tubeless strategies. However, postoperative pneumothorax is a primary limiting factor for such strategies. Accordingly, we evaluated the safety and efficacy of the prophylactic use of an air-extraction catheter as an improved drainage strategy and compared the findings with those for chest tube drainage in patients undergoing thoracic wedge resection. Patients undergoing thoracic wedge resection between August 2017 and October 2018 were enrolled in this single-center, randomized, open-label, noninferiority trial. Patients who received an improved drainage strategy involving the use of a prophylactic air-extraction catheter were randomized to the intervention group, whereas those who underwent routine chest tube drainage were assigned to the control group. Analysis was based on the per-protocol population. The primary outcome was the incidence of pneumothorax on postoperative day 1. Secondary outcomes included patient recovery and related complications, including pleural effusion, lung infection, numeric rating scale score for pain, postoperative chest tube or catheter removal, postoperative hospitalization, and chest tube reinsertion. A total of 96 patients were randomized. Baseline demographic and clinical characteristics were similar between groups. The incidence of pneumothorax in the intervention and control groups was 10.0% and 9.1%, respectively (noninferiority, P = 1.00). In addition, there were no significant between-group differences in secondary outcomes. A significantly lower pain score was observed in the intervention group (P = .001). The improved drainage strategy is not inferior to standard chest tube drainage after thoracic wedge resection and should be popularized.